Kesulitan Belajar Jarak Jauh Materi Tema 6 Panas dan Perpindahannya Suhu dan Kalor - Ahmad Muhandis Widodo; Fine Reffiane; Kiswoyo Kiswoyo (STKIP Andi Matappa Pangkep, 2023)
The purpose of this study was to find out the learning difficulties experienced by fifth grade students when learning through an online learning system at SD N Krompakan, Gemuh District, Kendal Regency.The research method used is qualitative research. In this study the data collection techniques used included interviews, questionnaires and documentation. This research was carried out at Krompakan Elementary School, Gemuh District, Kendal Regency in January 2023. In this study, data validity and triangulation tests were tested. The results of this study indicated that the analysis of distance learning difficulties for fifth grade students at Krompakan Elementary School had gone well.